Impact of Inclusive Leadership on Innovation Performance During Coronavirus Disease 2019 Outbreak: Mediating Role of Employee Innovation Behavior and Moderating Role of Psychological Empowerment - Gupta, Shuchi; Nawaz, Nishad; Tripathi, Abhishek; Arif Chaudhry, Shafaq; Agrawal, Khushbu (Frontiers in Psychology, 2022)
This study investigates the effect of inclusive leadership on innovation performance with a mediating role of employee innovation behavior and the moderating role of psychological empowerment (PE). Supervisors and employees of Saudi manufacturing firms are the participants of this study. This study used a quantitative research technique with a cross-sectional approach and a self-administrative survey questionnaire to collect the data. The data were analyzed by using the Smart PLS 3 software. The results depict that inclusive leadership has a significant positive impact on the firm’s innovation performance. Employees’ innovation behavior has a significant mediating effect on the association of inclusive leadership and innovation performance. Findings revealed that PE has an important moderating role in the association of inclusive leadership and innovation performance. The findings of this study contribute to the body of knowledge by finding that inclusive leadership has a significant effect on the firm’s innovative performance and PE is crucial to enhance innovation performance.